The Effect of Using a Dynamic Wrist Splint on Wrist Pain in Stroke Patients - Rachmat, Nur; Kuncoro, Bambang; Prasetya, Hanung (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Hand movement function in hemiplegic stroke patients is impaired due to contractures and spasticity. Pain in the wrist joint often occurs when moved. This research aims to determine how dynamic wrist splints can reduce wrist pain in stroke patients. Subjects and Method: This was a quasi-experimental study. The subjects were 20 hemiplegic stroke patients in Colomadu Karanganyar. The research was carried out in July – September 2023. The dependent variable was wrist pain. The independent variable was the use of a dynamic wrist splint. measurement the degree of pain using the Visual Analog Scale which is used to determine the level of pain felt by the sufferer. Data normality test using Shapiro-Wilk. The statistical test used in this research is wilxocon. Results: The ages of subjects ranged from 30 to 62 years. Wrist pain was reduced after the use of a dynamic wrist splint compared to levels before its use. Conclusion: There is an influence of dynamic wrist splints on wrist pain in stroke patients.